Factors Associated with the Achievement of Rotavirus Immunization in the Working Area of Limboto Public Health Center - Sukmawaty Tuna; Andi Akifa Sudirman; Dewi Modjo (Universitas Muhammadiyah Palu, 2026)
Rotavirus is a leading cause of severe diarrhea among children globally, including in Indonesia, where the prevalence of diarrhea in children under five reaches 9.8% (SSGI 2021). Diarrhea contributes as the second leading cause of death after pneumonia among children aged 29 days–11 months (9.8%) and toddlers aged 12–59 months (4.55%). Rotavirus (RV) immunization is recommended by WHO and ITAGI as an effective preventive measure, yet its coverage in Indonesia remains low (5.4% of the 16% target as of March 2025). Based on a preliminary survey at Limboto Health Center, Gorontalo Regency, the RV immunization coverage in 2024 was 71.2%, with findings showing that parents did not fully understand the benefits of RV. This study aims to examine the factors associated with the achievement of Rotavirus Immunization among infants aged 6–12 months in the working area of Limboto Health Center, Gorontalo Regency. The research method used was observational analytic research with a cross-sectional approach in the working area of Limboto Health Center. Population: 718 parents of infants aged 6–12 months. Sample: 88 respondents. Data were collected through questionnaires and observations of the Maternal and Child Health (MCH) handbook and analyzed using univariate and bivariate (Chi-Square test) analyses. Results: There was a significant relationship between education and RV immunization coverage (p-value = 0.013), knowledge and RV immunization coverage (p-value = 0.000), and the role of health workers and RV immunization coverage (p-value = 0.001). Conclusion: Educational level, knowledge, and the role of health workers are significantly associated with Rotavirus immunization coverage among infants aged 6–12 months at Limboto Health Center. Efforts to increase RV coverage should focus on educating parents (especially those with lower education levels) and optimizing the role of health workers as communicators, motivators, and facilitators.